The Cambridge Introduction to Toni Morrison / [electronic resource] - Roynon, Tessa (Cambridge : Cambridge University Press, 2012)
Toni Morrison has written some of the most significant and demanding fiction of the modern age. Her dazzling depictions of African-American experience are studied in high schools and colleges, debated in the media and analyzed by scholars at an astounding rate. This Introduction offers readers a guide to the world of Morrison in all its complexity, from her status as a key player on the global intellectual stage to her unique perspective on American history and her innovative narrative techniques. Covering every novel from The Bluest Eye to A Mercy, Tessa Roynon combines close readings with critical insights into Morrison's other creative work, such as short stories, libretto and song lyrics and unpublished pieces for performance. Lively and accessibly written, Roynon's insightful text is ideal for readers approaching Morrison for the first time as well as those familiar with her work.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).